Condições de trabalho e qualidade de vida na utilização de agrotóxicos no setor florestal - Caçador, Silvio Sérgio (2018)
The study of Quality of Life presents itself as a strategic tool to identify personal dissatisfaction and its effects, aiming at Occupational Safety and Health. The objective of this study was to characterize the profile, the conditions of the work and to analyze the quality of life, according to the point of view of 136 forest workers working with the handling and application of pesticides in Eucalyptus plantations, in 32 small Rural properties located in the South region of the Holy Spirit State. Qualitative research was carried out, applying a questionnaire previously prepared, in individual interviews, from a fixed relationship of issues. The evaluation of the quality of life was carried out with reference to those recommended by the methodology WHOQOL-bref and were identified the attributes that characterize the different perceptions of the group Studied. The work safety assessment was carried out in accordance with the guidelines for inspection of forest work proposed by the International Labor Organization, based on item 31.8 (Pesticides, Adjuvants and Related Products) of Regulatory Standard 31 - Occupational Safety and Health in Agriculture, Forestry, Forestry and Aquaculture. The results identified positive aspects, but also pointed out negative points regarding the supply and use of individual protection equipment, handling, storage and transport of Pesticides. In the conditions under which this study was conducted, it is concluded that: for the most part, forest workers are male, young, of rural origin, with low schooling and income below the national average; The inadequate conditions relating to safety at work are related to the lack of information, both technical and legal; The training mechanisms are insufficient and the activity is insecure; The group studied presents an average level of satisfaction with their quality of life (54.01%).